2012
DOI: 10.1017/s0021859612000895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sowing date and variety on yield and weed populations in a lentil–barley mixture

Abstract: SUMMARYThe present study examined variation in sowing date on lentils (Lens culinaris) in a standard lentil–barley (Hordeum vulgare) mixed cropping system in the temperate climate of central Europe to determine the effect on crop yield and weed control. A 2-year (2009/10) field experiment was carried out at the organic research station Kleinhohenheim (KH) and at the conventional research station Oberer Lindenhof (OLI) of the University Hohenheim, southwest Germany. The crop was sown at three dates in the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(20 reference statements)
2
6
0
Order By: Relevance
“…Anicia in 2016 (3.11 t ha −1 ). This yield is consistent with that (3.0 t ha −1 ) observed by Wang et al (2013) in an experiment conducted with cv. Anicia in organic farming in Germany without water stress.…”
Section: Yield Gap Analysis Of All Cultivars and Years Combinedsupporting
confidence: 92%
See 2 more Smart Citations
“…Anicia in 2016 (3.11 t ha −1 ). This yield is consistent with that (3.0 t ha −1 ) observed by Wang et al (2013) in an experiment conducted with cv. Anicia in organic farming in Germany without water stress.…”
Section: Yield Gap Analysis Of All Cultivars and Years Combinedsupporting
confidence: 92%
“…This highlights that spring wheat added at a low density (17% of sole crop density) was still dense enough to decrease the associated lentil yield, illustrating strong interspecific competition of spring wheat with lentil. Similar trends were observed in several previous studies of lentil-wheat intercrops (Akter et al 2004;Carr et al 1995;Wang et al 2013). Actual yield of lentil in sole crop and intercrop was significantly higher in 2016 than in 2015 (P < 0.001 and P < 0.01, respectively) ( Fig.…”
Section: Effect Of Intercrops On Actual Yieldsupporting
confidence: 90%
See 1 more Smart Citation
“…In turn, the timing of the harvest of monsoonal rice and underlying soil moisture content determine when the land is available to sow the following lentil crop. Time of sowing is very important for lentil growth to maximize yield (Silim et al 1991;Miah & Rahman 1993;Wang et al 2013) and it differs with the weather and between locations (Ali et al 2009). Ali et al (1993) demonstrated in multiple lentil sowingdate trials in India that late sowing had a severe yield penalty.…”
Section: Discussionmentioning
confidence: 99%
“…The monsoonal rice harvest period is between November and early December, often resulting in a delay in lentil sowing of up to 3 weeks to allow for optimum moisture conditions and land preparation (Ali et al 2005). However, as sowing date is critical for successful lentil cropping (Silim et al 1991;Wang et al 2013), this delay can result in reduced yields.…”
Section: Introductionmentioning
confidence: 99%